2011
DOI: 10.1089/jamp.2010.0815
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Exhaled Breath Particles from Healthy and Human Rhinovirus-Infected Subjects

Abstract: Background: Exhaled breath studies suggest that humans exhale fine particles during tidal breathing, but little is known of their physical origin in the respiratory system during health or disease. Methods: Particles generated by 3 healthy and 16 human rhinovirus (HRV)-infected subjects were counted using an optical particle counter with nominal diameter-size bins ranging between 0.3 and 10 mm. Data were collected from HRV-infected subjects during tidal breathing. In addition, data from healthy subjects were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
169
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 36 publications
6
169
1
1
Order By: Relevance
“…Larger particles are thought to be created by shear forces acting on fluid‐covered upper airways, where air velocities are much higher than in the deeper regions. This phenomenon is thought to occur primarily during coughing because the air flow rates are much higher than during breathing 29, 30, 31. Since, in this theory, deep lung particle generation occurs during both breathing and coughing while upper airway particle generation occurs only during coughing, then the modest increase in the number of positive samples seen during coughing compared to exhalation in our experiments supports the idea that much of the infectious aerosol is originating in the deep lung regions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Larger particles are thought to be created by shear forces acting on fluid‐covered upper airways, where air velocities are much higher than in the deeper regions. This phenomenon is thought to occur primarily during coughing because the air flow rates are much higher than during breathing 29, 30, 31. Since, in this theory, deep lung particle generation occurs during both breathing and coughing while upper airway particle generation occurs only during coughing, then the modest increase in the number of positive samples seen during coughing compared to exhalation in our experiments supports the idea that much of the infectious aerosol is originating in the deep lung regions.…”
Section: Discussionsupporting
confidence: 77%
“…Humans produce more aerosol particles when they cough vs. when they exhale 27, 28. Most of the aerosol particles produced during normal breathing are thought to originate deep in the respiratory tract, while coughing may produce aerosol both from the lower airways and also from the upper airways 29, 30, 31. Thus, if coughing produces much more infectious aerosol than exhaling, this would suggest that much of the virus in cough‐generated particles may be coming from the upper airways.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those reported by others; virtually all studies of human aerosol particle generation that have compared subjects have found tremendous person-to-person variation. (8)(9)(10)(11)(12)(13) This phenomenon may lead to a "superspreader" effect; that is, if some people produce much greater quantities of infectious aerosols, they may be much more likely to spread influenza to others. (9,18) The cough aerosol particle volume also varied greatly from patient to patient; the average aerosol volumes ranged from 2.4 to 144 pL/cough when ill and 0.5 to 145 pL/cough after recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Fabian et al (11) tested 10 patients with influenza and found that the concentration of particles exhaled by these subjects ranged from 67 to 8500 particles/liter of air; similar results were later reported for patients with rhinovirus infections. (13) Almstrand et al (15) also found that the exhaled particle concentrations varied considerably from subject to subject and with the depth of breathing, but that the exhaled concentrations for each subject were fairly consistent during repeated testing for each respiratory maneuver studied.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation